Towards a standard-based open data ecosystem: analysis of DCAT-AP use at national and European level. (13th January 2022) - Barthelemy, Florian; Cochez, Michael; Dimitriadis, Iraklis; Karim, Naila; Loutas, Nikolaos; Magnisalis, Ioannis; Comet, Lina Molinas; Peristeras, Vassilios; Wyns, Brecht
In Europe, an open government data ecosystem is being developed. This ecosystem is implemented using various technologies and platforms. In fact, the use of a common metadata standard for describing datasets and open data portals, i.e., the DCAT-AP specification, appears as the lingua franca that connects an, otherwise, fragmented environment. In this context, the standard-based consolidation of open data promotes the subsidiarity principle, allowing open data portal owners to choose platforms and internal representations based on their specific requirements. However, the portal owners must provide an export with DCAT-AP compliant metadata about the dataset they store. In this paper we provide a detailed study of how the DCAT-AP specification is used in practice, both at the national and the European level. Consequently, we also identify issues, challenges, and opportunities for improvements that can be used as input for the next revision cycle of the standard. Essentially, our goal is to contribute towards the enrichment of a growing and promising European open data ecosystem.